Cultural Ecosystem Services in Urban Green Areas: Assessment Methods and Contributions to Sustainable Urban Planning - Mattos , Eluana Claudia Medeiros; Pereira , Rodrigo Kuestra; Quaresma, Cristiano Capellani (Technical and Scientific Journal Green Cities, 2025)
Objective – To map, analyze, and classify the scientific production on Cultural Ecosystem Services (CES) in urban green areas, published between 2010 and 2025, with emphasis on the methodologies employed for their measurement and assessment. Methodology – This is an exploratory and descriptive study, with a qualitative and quantitative approach, based on a systematic literature review. The research was preceded by a bibliometric review and supported by content analysis. The search in the Web of Science database yielded 237 records, of which 152 composed the final corpus after applying inclusion criteria and screening with the Rayyan software. Statistical analyses, co-authorship network analyses, and trend analyses were conducted using VOSviewer and the Bibliometrix R-package, and were subsequently complemented by content analysis aimed at classifying the methodological instruments employed in the measurement and evaluation of Cultural Ecosystem Services (CES). Originality/Relevance – The study addresses the lack of consistent systematizations of techniques applied to CES assessment, a field that, despite its growth, still lacks methodological standardization and geographical diversity. It stands out for integrating bibliometric and content analysis methods, providing a comprehensive and critical perspective on evaluation practices. Results – A significant increase in publications was observed from 2018 onwards, with a projection of 31 articles for 2025 (R² = 0.897). Quantitative approaches predominate (56.6%), followed by mixed methods (32.2%) and qualitative ones (11.2%). Eleven categories of methodological instruments were identified, with emphasis on Likert-scale surveys (31.6%), text mining and social network analysis (20.4%), and spatial indicators (18.4%). Theoretical/Methodological Contributions – The study systematizes and organizes different approaches to CES assessment in urban areas, offering a novel comparative framework that can guide future research and management practices, as well as support the development of replicable protocols across multiple contexts. Social and Environmental Contributions – By highlighting regional inequalities and the underrepresentation of Latin America and Africa, the study reinforces the need to expand scientific production in the Global South. Its findings contribute to strengthening public policies, promoting environmental justice, and fostering the integration of city, landscape, and nature, in line with the Sustainable Development Goals.